Implementing marine ecosystem-based management: lessons from Australia. (12th July 2017) - Smith, David C.; Fulton, Elizabeth A.; Apfel, Petrina; Cresswell, Ian D.; Gillanders, Bronwyn M.; Haward, Marcus; Sainsbury, Keith J.; Smith, Anthony D. M.; Vince, Joanna; Ward, Tim M.
Abstract: Ecosystem-based management (EBM) is now widely accepted as the best means of managing the complex interactions in marine systems. However, progress towards implementing and operationalizing it has been slow. We take a pragmatic approach to EBM. Our simple definition is balancing human activities and environmental stewardship in a multiple-use context. In this paper, we present case studies on the development and implementation of EBM in Australia. The case studies (Australia's Ocean Policy, the Great Barrier Reef, New South Wales (NSW) marine estate, Gladstone Harbour, and South Australia and Spencer Gulf) span different spatial scales, from national to regional to local. They also cover different levels of governance or legislated mandate. We identify the key learnings, necessary components and future needs to support better implementation. These include requirements for clearly identified needs and objectives, stakeholder ownership, well defined governance frameworks, and scientific tools to deal with conflicts and trade-offs. Without all these components, multi-sector management will be difficult and there will be a tendency to maintain a focus on single sectors. While the need to manage individual sectors remains important and is often challenging, this alone will not necessarily ensure sustainable management of marine systems confronted by increasing cumulative impacts.